1985
DOI: 10.1111/j.1365-3059.1985.tb01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Botrytis spp. occurring on onions (Allium cepa) and leeks (Allium porrum)

Abstract: Botrytis byssoidea (mycelial neck rot) was more prevalent than B. allii (sclerotial neck rot) on the leaves of field onions and the bulbs of stored onions grown in some of the areas where onions or onions and leeks had previously been grown sequentially. B. byssoidea and B. porri were also isolated from leeks. Spores of B. allii, B. byssoidea (from onions and leeks), B. porri, and B. squamosa caused infection of seedlings of salad (green) and bulb onions. Inoculation with B. squamosa spores caused severe infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…However morphological differences seen in Botrytis spp. isolated from a single plant also might be an indication of several different Botrytis species specialized to infect a common host, as seen with neck rot of onion (Allium cepa L.) (Presly 1985).…”
Section: Introductionmentioning
confidence: 99%
“…However morphological differences seen in Botrytis spp. isolated from a single plant also might be an indication of several different Botrytis species specialized to infect a common host, as seen with neck rot of onion (Allium cepa L.) (Presly 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Until the recent taxonomic and nomenclatural clarification of these neck rot species by Yohalem et al (76), B. aclada was considered by many to be synonymous with B. allii, while B. byssoidea was regarded by some as conspecific with B. aclada (23). The lack of distinction of these species was due, in part, to limitations at differentiating these species using classical morphological and cultural methods (47,48). Nonetheless, Owen et al (42) demonstrated that B. byssoidea and B. aclada are valid species.…”
mentioning
confidence: 97%
“…However, the two species are difficult to distinguish morphologically, with similar growth patterns on agar media and overlapping spore sizes (7, 76). B. byssoidea is occasionally reported as causing neck rot (47,73). However, the true impact of B. byssoidea may be underestimated because of difficulty in isolating and identifying this species, which sporulates sparsely on most common media used to isolate fungi from plant tissues (7).…”
mentioning
confidence: 99%
“…Generally B. allii is considered to be the more prevalent species in many countries (Walker, 1925;Goidanich, 1964;Tichelaar, 1967;Presly, 1985). The fungus is mainly seed transmitted, although, to a lesser extent, sclerotia, infected debris and cull piles are also responsible for initiation of primary infection (Walker, 1925(Walker, , 1926Maude & Presly, 1977b).…”
Section: Introductionmentioning
confidence: 99%